Spatio-temporal variability of Gladiolus imbricatus L. populations in different plant communities near Kraków - Kostrakiewicz-Gierałt, Kinga (Ecological Questions, 2017)
The investigations, aimed to assess the abundance, stage structure and distribution of shoots, as well as the chosen traits of generative shoots (number of leaves and length of the longest one, height of shoot, length of inflorescence and the dorsal tepal of the lowermost flower, number of seed capsules) of Gladiolus imbricatus L. were conducted in the years 2015–2017. The observations were carried out from Kraków-Pychowice to Tyniec in abandoned moor-grass meadow (Patch I), shrub willows (Patch II), macroforb community (Patch III) and community dominated by tall-growing grasses (Patch IV). The population abundance augmented gradually in subsequent study sites. Additionally, the temporal fluctuations of shoot number were recorded in all the Patches. The similar in consecutive years’ stage structure differs among the study sites. The occurrence of juvenile, vegetative and generative shoots in Patch I might suggest the successful seedling recruitment, while the lack of shoots in pregenerative stages in Patches II-IV might indicate the absence of safe sites for the appearance of new genets. The occurrence of clusters of shoots in Patches II-IV might be a consequence of clonal growth. The traits of generative shoots rather did not show the temporal variability, but they presented spatial variability and in most cases augmented from Patch I, via Patches II and III, to Patch IV. The performed studies enabled ascertaining that the population occurring in Patch I presents the best condition despite the lowest abundance of shoots. Also the other, more abundant populations, inhabiting Patches II-IV might persist in the colonised sites thanks to the vegetative multiplication of ramets and maximisation of chances for successful pollination and effective seed dissemination.